Analisis Permasalahan Pelaksanaan Pembelajaran Matematika di Kelas V SD X Simawang Kecamatan Rambatan - Meliza Silvi; Safrizal Safrizal; Zulhendri Zulhendri (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2023)
The The purpose of this research is to find out the problems of implementing mathematics learning in class V to X Simawang, Rambatan District. This study uses a qualitative research method with a case study research type. The first data collection technique is through observation, the second is interview and the third is documentation with the aim of obtaining information directly from teachers and students regarding the problems that arise in the implementation of learning mathematics. The data collected was then analyzed using the Miles and Huberman model which consisted of three steps, namely data reduction, data display, and conclusions. So that researchers can find various problems found in the field regarding the problems of implementing mathematics learning including, students do not understand and do not make assignments, students think that mathematics is difficult and makes them dizzy, there is no media during the learning process, students do not pay attention to teachers, teachers only use conventional learning approaches. So that the data that the researchers found was tested, the researchers carried out techniques to guarantee the validity of the data.